2016
DOI: 10.1093/abbs/gmv127
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-140 regulates cell growth and invasion in pancreatic duct adenocarcinoma by targeting iASPP

Abstract: MicroRNAs are ∼22 nucleotide RNAs processed from RNA hairpin structures that play important roles in regulating protein expression level via binding to mRNA, either suppressing its translation or speeding up its degradation. In humans, they regulate most protein-coding genes, including genes important in cancer and other diseases. In this study, the expression of microRNA-140 (miR-140) was demonstrated to be significantly suppressed in pancreatic duct adenocarcinoma specimens and cell lines, compared with thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…Numerous studies have reported that miR-140 was frequently deregulated in various types of cancers. Reduced expression levels of miR-140 has been demonstrated in pancreatic duct adenocarcinoma (29), lung (30,31), colorectal (32), ovarian (33), esophageal (34) and tongue cancer (35). However, miR-140 also has been found upregulated in spinal chordoma (36) and breast cancer (37).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have reported that miR-140 was frequently deregulated in various types of cancers. Reduced expression levels of miR-140 has been demonstrated in pancreatic duct adenocarcinoma (29), lung (30,31), colorectal (32), ovarian (33), esophageal (34) and tongue cancer (35). However, miR-140 also has been found upregulated in spinal chordoma (36) and breast cancer (37).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, miR-140 overexpression suppressed non-small cell lung cancer growth and metastasis in vivo (39). Liang et al found that ectopic of miR-140 expression decreased pancreatic duct adenocarcinoma cell growth and invasion (29). Zhang et al demonstrated that miR-140 acted as a tumor suppressor in colorectal cancer by inhibiting cell proliferation, migration and invasion (32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Iida et al 119 reported that upregulating miR-125b could suppress P53-dependent apoptosis and induce chemoresistance to doxorubicine, vincristine, etoposide and mafosfamide in Ewing sarcoma/primitive neuroectodermal tumor (EWS) cells. Liang and colleagues 120 demonstrated that overexpression of miR-140 could interfere with the growth and invasion of pancreatic duct adenocarcinoma cells by directly targeting inhibitor of apoptosis-stimulating protein of P53 (iASPP). MiR-122/cyclin G1 interaction was demonstrated to positively regulated P53 protein stability and transcriptional activity and affected doxorubicin sensitivity of human hepatocarcinoma cells 121 .…”
Section: Aberrant Expression Of Mirnas and Cancer Drug Resistancementioning
confidence: 99%
“…In western industrialized countries, PCa is generally considered as the common malignant disease and the second most common cause of cancer-related death among men. 30 However, the miR-140 prognostic relevance and effects in PCa are not clear. 22-24 YES1, a notable member of Src family tyrosinekinases, and has been widely documented to regulate cell growth, adhesion, and F I G U R E 4 miR-140 directly targets the 3′-UTR of YES1 mRNA.…”
Section: Discussionmentioning
confidence: 99%